Multiscale and multiphysics production forecasts of shale gas reservoirs: New simulation scheme based on Gaussian pressure transients. (15th March 2023) - Afagwu, Clement; Alafnan, Saad; Weijermars, Ruud; Mahmoud, Mohamed
Highlights: Natural gas transport in shales follow advective and molecular diffusive mechanisms. The transport model is defined based on the shale matrix characteristics. Gaussian Pressure Transient is used as an upscaling forward simulation method. The transport could shift from advection to molecular diffusion during the depletion scheme. The production rate is influenced by pore compaction and local heterogeneity. Abstract: Common numerical solutions for production rate forecasting of shale reservoirs have a limited capability to describe the dynamics of fluid mass transfer during a pressure depletion cycle due to production with hydraulically fractured well systems. The pressure drawdown imposed by the well system triggers continuous expansion of free gas in the larger pores, while molecular diffusion predominates in the smaller pores. The declining reservoir pressure leads to the closure of larger pores, which gives further significance to molecular diffusion as a component of the mass transport process. To capture these multiphysics mechanisms, pressure-diffusion and molecular-diffusion forms of the diffusivity equation, discretized in space and time, were simultaneously solved to simulate mass transfer dynamics and kinematics in shale formations. This new approach uses a Gaussian probability function to describe the advance rate of both types of diffusion processes, creating a unique scheme for simulating shale gas reservoirs based on physical parameters that could be either measured or characterized. The adopted algorithms successfully provide solutions that can match the typical shale production profiles. Results are sensitive to the essential reservoir parameters of pressure depletion, matrix permeability, organic content, and local heterogeneity. The simultaneous solution of molecular and pressure diffusivity equations reveals their interdependencies. The production peaks early and then rapidly declines with a growing effect of pore compaction. The flux of the sorbed phase contributes to the production rate by some factor that is determined by the sorption capacity of the organic matter. The methodology provided in this study can be utilized to simulate mass transport in shale reservoirs and predict hydrocarbon production rates, which may greatly aid asset management decisions and maximization of the ultimate recovery.